On Perspectiving in Cognitive Grammar and Communicative Dynamism - Sunarto, Emanuel (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2012)
The article is concerned with the concept of perspective in Cognitive Grammar and Communicative Dynamism. To the former, perspective is understood in the realm of cognitive concepts such as space, motion, locationality, directionality, importance, and focus ascribable to a particular sentence segment. To the latter, perspectiving is a matter of valuating, viz. assigning informational value to a sentence segment as a part of a distributional field of communicative dynamism. The two streams of thought evidently hold different constructs per-taining to the term perspective: conceptual-categorial on the one hand, and functional-informational on the other. However, the two seem to agree when perspectiving is concerned with the notion of importance and focus or rhematization.